Rock and roll a social history - Friedlander, Paul 1951- (Westview Press, 1996)
An overview of rock and roll's first thirty-five years.
Keywords: Geschichte; Rock (Musique) - Histoire et critique; Rock (musique) - Histoire et musique; Rock-'n-roll; Sociale aspecten; Gesellschaft; Rock music -- History and criticism; Rockmusik; Sozialgeschichte